EFFECTIVENESS OF JIGSAW TECHNIQUE GROUP GUIDANCE TO INCREASE STUDENTS' CAREER EXPLORATION - Siswoko, Heri; Eliasa, Eva Imania; Fauzi, Lailla Affianti (Universitas Labuhanbatu, 2025)
Purpose-This study examines the effectiveness of the Jigsaw technique group guidance guide in improving students' career exploration at SMP Negeri Bontang. Career exploration is an important process in student development, especially at the junior high school level, where students begin to recognize their potential, interests, talents, and personal values while exploring relevant career opportunities. An effective career exploration process should be systematically designed through supportive services such as career guidance and interactive approaches, such as the Jigsaw technique, that encourage the development of communication, cooperation, and decision-making skills.Methodology-The Jigsaw technique can be a practical approach in group guidance services to support career exploration. This study used a quasi-experimental method with a control and experimental group design. The research subjects involved 30 students of SMPN 1 Bontang as the control group and 30 SMPN 3 Bontang as the experimental group. Data collection techniques used a career exploration scale questionnaire, while data analysis used the Wilcoxon Signed Rank Test and N-Gain test.Findings-The results showed that the effectiveness of the Jigsaw technique group guidance guide positively influenced students' career exploration. Based on calculations using the Wilcoxon Signed Rank Test, a significance value of 0.00 was obtained, below 0.05, indicating a significant difference between the pre-test and post-test results of the Jigsaw technique group guidance service. In addition, the calculation of the gain score shows a value of 0.67, which puts the guide's effectiveness in the medium category. Thus, this Jigsaw technique group guidance guide is declared effective enough to increase the career exploration of Bontang City Public Junior High School students.Significance- The implementation of group guidance services that support career exploration is often not optimal, mainly due to the unavailability of well-structured guidelines.Keywords: Group guidance guide, Jigsaw technique, Career exploration